Energy efficient beamforming scheme for wireless sensor networks - Zhi-chao QIN; Zheng ZHOU; Xiao-chuan ZHAO (Tongxin xuebao)
Aiming at the limitation of energy and communication distance for nodes in wireless sensor networks and the characteristics of premature death due to ignoring the energy balance for traditional beamforming schemes,an energy efficient beamforming scheme was proposed.First the impact of the number of nodes,the transmission coefficients,the limited power,and the arrival phase on the network energy consumption is analyzed,and the corresponding design principles are given.Then,the nodes which participate the beamforming are selected based on these principles their transmission coefficients are adjusted according to their residual energy and phase.The analysis and simulation results show that the proposed scheme can effectively increase the number of successful transmission,balance the energy consumption among the nodes and prolong the network lifet me.